Properties of particleboard from admixture of petai belalang (leucaena leucocephala) and kenaf core (hibiscus cannabinus l.) particles / Khairul Azhar Johari, Jamaludin Kasim and Wan Mohd Nazri Wan Abdul Rahman - Johari, Khairul Azhar; Kasim, Jamaludin; Wan Abdul Rahman, Wan Mohd Nazri (2012)
The objective of this study was to determine the properties of particleboard from mix Kenaf core with Petai Belalang at different mixing ratio of (10:90), (30:70) and (50:50). Particleboard was produced in homogenous board with size of particle 2.0 mm until 0.5mm. The target density of the board was 700 kg/m3 . The board was bonded using Urea Formaldehyde (UF) as the resin and resin content of 7%. In the study particleboards made with 50% kenaf core showed the lowest properties of MOR, MOE, IB and worst TS value. Addition of kenaf core was found to significantly affect the MOR, MOE, IB and TS values. Boards made with at least 10% kenaf core were able to surpassed the minimum requirement of EN STO for MOR, MOE and IB. However, all boards failed to meet the minimum requirements of 12% for the TS.